Five Years of an Enlarged EU A Positive Sum Game - Keereman, Filip; Szekely, Istvan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book analyzes the economic performance of the EU in the first five years after its largest expansion in 2004. Accession and integration were expected to foster growth and convergence among the new Member States through intensified trade, foreign direct investment, financial deepening and the adoption of the EU's institutional framework. With the benefit of five years experience, this book brings together experts from academia and think-tanks to assess the driving forces of economic growth and real convergence. The question whether the EU has made a difference in terms of growth is studied thoroughly from various angles, including that of country-specific and sector-specific analysis. It is shown that while the enlargement has been a success story overall, growth and catching-up cannot be taken for granted and the importance of economic policy remains undiminished.
Overview -- Overview -- Trade and Foreign Direct Investment in an Enlarged EU: Opportunities and Challenges -- Evolving Pattern of Intra-industry Trade Specialization of the New Member States of the EU: The Case of the Automotive Industry -- FDI Spillovers in the Czech Republic: Takeovers Versus Greenfields -- Comments on Chapter 2 and 3 -- Migration in an enlarged EU: solution or problem for labour market woes and cash-strapped social security systems? -- Migration in an Enlarged EU: A Challenging Solution? -- The Consistency of EU Foreign Policies Towards New Member States -- Comments on Chapters 5 and 6 -- Financial integration and stability in an enlarged EU -- Real Convergence, Financial Markets, and the Current Account: Emerging Europe Versus Emerging Asia -- Sustainable Real Exchange Rates in the New EU Member States: Is FDI a Mixed Blessing? -- Comments on Chapters 8 and 9 -- Integration, Openness and Growth: Did Accession Make a Difference? -- The Second Transition: Eastern Europe in Perspective -- An Evaluation of the EU$1 (Bs Fifth Enlargement with Special Focus on Bulgaria and Romania -- Comments on Chapters 11 and 12.s
Keywords: Economics; Economic policy; Europe -- Economic policy; Economics/Management Science; European Integration; Economic Policy